Keeping in touch with the visual system: spatial alignment and multisensory integration of visual-somatosensory inputs - Mahoney, Jeannette R.; Molholm, Sophie; Butler, John S.; Sehatpour, Pejman; Gomez-Ramirez, Manuel; Ritter, Walter; Foxe, John J. (Frontiers in Psychology, 2015)
Correlated sensory inputs coursing along the individual sensory processing hierarchies arrive at multisensory convergence zones in cortex where inputs are processed in an integrative manner. The exact hierarchical level of multisensory convergence zones and the timing of their inputs are still under debate, although increasingly, evidence points to multisensory integration at very early sensory processing levels. The objective of the current study was to determine, both psychophysically and electrophysiologically, whether differential visual-somatosensory integration patterns exist for stimuli presented to the same versus opposite hemifields. Using high-density electrical mapping and complementary psychophysical data, we examined multisensory integrative processing for combinations of visual and somatosensory inputs presented to both left and right spatial locations. We assessed how early during sensory processing visual-somatosensory (VS) interactions were seen in the event-related potential and whether spatial alignment of the visual and somatosensory elements resulted in differential integration effects. Reaction times to all VS pairings were significantly faster than those to the unisensory conditions, regardless of spatial alignment, pointing to engagement of integrative multisensory processing in all conditions. In support, electrophysiological results revealed significant differences between multisensory simultaneous VS and summed V+S responses, regardless of the spatial alignment of the constituent inputs. Nonetheless, multisensory effects were earlier in the aligned conditions, and were found to be particularly robust in the case of right-sided inputs (beginning at just 55ms). In contrast to previous work on audio-visual and audio-somatosensory inputs, the current work suggests a degree of spatial specificity to the earliest detectable multisensory integrative effects in response to visual-somatosensory pairings.